Drought frequency, intensity, and exposure have increased due to historical land use and land cover changes - Tao Tang; Jun Ge; Haiyun Shi; Lin Wang; Junji Cao; Xuhui Lee (Communications Earth & Environment)
Abstract Drought, a marked deficiency of surface water, has a wide adverse impact on the environment, agriculture, and the socio-economy. The global impact of land use changes on drought features and associated exposures to droughts, however, remains largely unknown. In this study, the changes of drought features are estimated by using the model simulations with and without land use change. We show that historical land use changes since 1850, mainly deforestation and crop expansion, has increased the drought frequency, duration, and severity over half of the global land area. Regions with greater activity tend to experience stronger exacerbation of drought events. Owing to their increasing frequency and prolonged duration, populations, croplands and forests are increasingly exposed to drought events, which poses serious potential impacts on human health, agriculture, and forest ecosystems. The enhanced drought events could be substantially alleviated by potential reforestation activity. Our results provide useful information for land-management-related policy-making.